Student perceptions of ICC development and the reasons for it during CASA@AUC - Wright, Stephen (AUC Knowledge Fountain, 2024)
Research has described how studying abroad has become a major goal in the Arabic world, focusing on understanding the ideas and way of life of another culture and people. Study abroad programs increase students' “Intercultural communicative competence” as indicated by researchers like Maharaja (2018) and Lee and Song (2019). The current study is a case study involving three participants. It focuses on students' perceptions of the influence of the CASA@AUC study abroad program on their intercultural communicative competence (ICC) as reflected by ACTFL performance indicators they are capable of executing. Results of the study indicate that they have reached advanced ICC levels, they also indicate that students attribute their ICC capabilities to the classes and cultural experiences they were exposed to as part of the CASA@AUC program. In addition, results reveal that interaction with members of the host culture is perceived by study participants as having a clear influence on their ICC capabilities. This study also highlights the influence of possible barriers to intercultural communicative competence, namely an excessive workload during study abroad.